PENGARUH NET PROFIT MARGIN, CURRENT RATIO DAN QUICK RATIO TERHADAP HARGA SAHAM PADA PT PERDANA GAPURAPRIMA Tbk PERIODE 2013-2022 - Firda Nur Azhar; Gatut Dradjad Purwoko (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Net Profit Margin on the share price of PT Perdana Gapuraprima Tbk for the 2013-2022 Period, Current Ratio on the share price of PT Perdana Gapuraprima Tbk for the 2013-2022 Period, Quick Ratio to the share price of PT Perdana Gapuraprima Tbk and Net Profit Margin, Current Ratio and Quick Ratio on the share price of PT Perdana Gapuraprima Tbk for the 2013-2022 period 2013-2022. This research method uses a descriptive quantitative research method. The research population used in this study is the financial statements of PT Perdana Gapuraprima Tbk for 10 years from 2013-2022. In this study, data analysis was used, namely descriptive statistical analysis, classical assumption tests (Normality Test, Heteroscedasticity Test, Aurocorrelation Test and Multicollinearity Test). Quantitative Analysis Test (Multiple Linear Regression, Correlation Coefficient Analysis, and Determination Coefficient Analysis), and Hypothesis Test (T Test and F Test). The results of the Net Profit Margin (NPM) test (T Test) partially did not have a significant effect on the stock price of 0.536 < ttable 2.36462 with a Sig. value of 0.615>0.05, Current Ratio (CR) partially affected the stock price with a sig. of 8.070 > ttable 2.36462 with a Sig. value of 0.000 < 0.05, Quick Ratio (QR) partially had a positive effect on the stock price with a calculation of 10,118 > ttable 2.36462 with a significant value of 0.000 < 0.05. Overall or simultaneously Net Profit Margin (NPM), Current Ratio (CR) and Quick Ratio (QR) all affect the stock price, this can be obtained from Fcal 63,447 > 4.47 with a value of Sig. 0.000 < 0.05 in PT Perdana Gapuraprima Tbk in 2013-2022.